2006
DOI: 10.1002/cbf.1343
|View full text |Cite
|
Sign up to set email alerts
|

MRP1/GS‐X pump ATPase expression: is this the explanation for the cytoprotection of the heart against oxidative stress‐induced redox imbalance in comparison to skeletal muscle cells?

Abstract: Striated muscle activity is always accompanied by oxidative stress (OxStress): the more intense muscle work and/or its duration, the more a redox imbalance may be attained. In spite of cardiac muscle functioning continuously, it is well known that the heart does not suffer from OxStress-induced damage over a broad physiological range. Although the expression of antioxidant enzymes may be of importance in defending heart muscle against OxStress, a series of combined antioxidant therapeutic approaches have prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…However, it did not reduce the DOX-induced increase in calcium response. Alternatively, DOX has been described to reduce GSH levels due to an extensive extrusion of GSH-conjugated DOX by MRPs (Krause et al, 2007). N-acetyl cysteine supplementation has been described to be capable of restoring GSH stores (Kelly, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it did not reduce the DOX-induced increase in calcium response. Alternatively, DOX has been described to reduce GSH levels due to an extensive extrusion of GSH-conjugated DOX by MRPs (Krause et al, 2007). N-acetyl cysteine supplementation has been described to be capable of restoring GSH stores (Kelly, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, results obtained are not completely conclusive (Singal et al, 1997). It has been described that DOX is extruded from the cardiac myocyte conjugated to GSH by multidrug resistance proteins (MRPs) (Krause et al, 2007). Extensive extrusion of DOX subsequently induces GSH depletion.…”
mentioning
confidence: 99%
“…In addition, cardiomyocytes were reported to have intrinsically low levels of antioxidant enzymes that may explain the potent protective function of monoHER in these cells (Hrdina et al, 2000). Also high activity of the MRP1/ GS-X pump in these cells was reported (Krause et al, 2007), which may export DOX as glutathione-Sconjugate out of the cells, thereby modifying its cytotoxic effects. However, previously we found that monoHER did not affect DOX levels in cardiac cells in mice or influence the biodistribution of DOX (Abou El Hassan et al, 2003b).…”
Section: Discussionmentioning
confidence: 92%
“…As GSH is the most important antioxidant systems that b-cells use against redox-threatening situations (for instance, in immunoinflammatory situations triggered by inflammatory cytokines (Krause et al 2007)), BRIN-BD11 cells were seeded into six-well plates (2!10 6 cells/well), allowed to adhere overnight, and then washed with PBS after which they were incubated in fresh media, containing 11 . 1 mM D-glucose and 2 mM L-glutamine, in the presence or absence of sublethal pro-inflammatory cytokine cocktail with different concentrations of L-arginine (above).…”
Section: Measurement Of Gsh and Glutathione Disulphide Contentmentioning
confidence: 99%
“…Afterward, cells were rinsed twice with PBS and disrupted in 200 ml of 5% (w/v) metaphosphoric acid on ice. After centrifugation (14 000 g, 5 min at room temperature), cell lysates were spectrophotometrically (415 nm) assayed on a temperature-controlled microplate reader (Molecular Devices SpectraMax Plus 384) by a modification of the 5,5 0 -dithiobis(2-nitrobenzoic acid) (DTNB)/glutathione disulphide (GSSG) reductase recycling method, using the N-ethylmaleimide conjugating technique for GSSG sample preparation (Krause et al 2007). Samples (10 ml) were assayed in 105 ml final volume in 96-well polystyrene plates at 37 8C in the presence of 10 mM DTNB, 0 .…”
Section: Measurement Of Gsh and Glutathione Disulphide Contentmentioning
confidence: 99%